1986
DOI: 10.2105/ajph.76.11.1345
|View full text |Cite
|
Sign up to set email alerts
|

The relationship of family income to the incidence, external causes, and outcomes of serious brain injury, San Diego County, California.

Abstract: Among residents of San Diego County, Califomia the incidence and external causes of serious brain injury were related to the median family income of the census tract of residency. Low income tracts had high incidence rates-a finding not changed by adjustment for age and race/ethnicity. For those injured, the type of emergency transport, time from injury to treatment, and outcome of treatment were not related to the median income of the census tract of residency. (Am J Public

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

1990
1990
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(22 citation statements)
references
References 5 publications
0
21
0
Order By: Relevance
“…Early estimates of anosmia following head injury suggested an incidence of 4-7%, though these reports varied widely in severity of injury as well as the methods used to assess the dysfunction [22][23][24][25][26]. In their 1991 review, Costanzo and Zasler reported anosmia in 25-30% of patients with severe head injury, 15-19% in those with moderate head injury, and 0-16% in those with mild injuries [27].…”
Section: Epidemiologymentioning
confidence: 99%
“…Early estimates of anosmia following head injury suggested an incidence of 4-7%, though these reports varied widely in severity of injury as well as the methods used to assess the dysfunction [22][23][24][25][26]. In their 1991 review, Costanzo and Zasler reported anosmia in 25-30% of patients with severe head injury, 15-19% in those with moderate head injury, and 0-16% in those with mild injuries [27].…”
Section: Epidemiologymentioning
confidence: 99%
“…Two studies used the same data source (Northern Manhattan Injury Surveillance System) to examine severe injuries (those resulting in hospitalization or death) but utilized two different levels of analysis: zip code of residence (23) and census tract (22). Both studies found that low SES was associated with higher injury rates among persons ages 16 and under. For the studies examining cause-specific nonfatal injuries, rates were higher in areas characterized by low SES, or inversely correlated with SES measures for head injuries (24,41,60), fire or burn injuries (32,47), pedestrian or bicyclist injuries (21,63), and intentional nonfatal injuries (28), regardless of study population and setting, source of data, covariates, or SES measure(s) used. Two of the individual-level studies examined the relationship between SES and nonfatal injuries by gender.…”
Section: Nonfatal Injuriesmentioning
confidence: 99%
“…-Age-specific brain injury incidence rates per 100 000 population for males and females, selected US studies. (7) 185 (100) 5 (2) 229 (100) 5 (2) 241 (100) 43 (8) 525 (99) 68 (5) 1234 (101) »Dead on arrival (DOA) includes those dead at the scene or pronounced dead at the emergency facility. Severity There are no published reports avail¬ able that deal with severity of brain in¬ juries for children except the San Diego County report of 1981,8 which is limited to those aged 0 to 15 years.…”
Section: Socioeconomic Statusmentioning
confidence: 99%
“…If the US population of persons aged 0 to 19 years in 1985 was 74 255 000, and we assume (1) severity proportions of 86% mild, 8% moderate, and 6% severe; (2) in-hospital case-fatality rates of 0, 2, and 42 per 100 patients, respectively, by severity; and (3) disability rates (any neurologic limi¬ tation or disability on hospital dis¬ charge) of 10%, 90%, and 100% for mild, moderate, and severe brain injuries, respectively, then about 29 000 persons aged 0 to 19 years have a resultant dis¬ ability each year from a brain injury.…”
Section: Disabilitiesmentioning
confidence: 99%